Penggunaan Marka DNA dalam Seleksi Induk Ikan Kerapu Macan (Epinephelus fuscoguttatus) yang Tahan Terhadap Bakteri Vibrio alginolyticus (Torani Journal of Fisheries and Marine Science, 2016)
The objective of the present study was to use selected RAPD markers (Primer UBC-122 and YNZ-22) in parental selection to the bacterial Vibrio alginolyticus resistance in Tiger groupers (Epinephelus fuscoguttatus).  Eighteen fish parent samples were challenged with Vibrio alginolyticus and parental selection was examined by a PCR-RAPD method.   The results showed that from 18 fish samples, primer YNZ-22 generated 18 fragments while primer UBC-122 generated 8 fragments only (KHP, KB, HB, PB, MKH, MH, K and MK).  In addition, the average number of fragments from each samples generated from primer-YNZ was higher (3,2) than from UBC-122 (2,3). This indicates that primer YNZ-22 is better than primer UBC-122 to use in parental selection to the Vibrio alginolyticus resistance in Tiger groupers.  From the parental selection, five fish parents (KHP, PB, MH, K and  MK) were selected for their high resistance to the bacterial Vibrio alginolyticus.